Decreased calpain 6 expression is associated with tumorigenesis and poor prognosis in HNSCC - Xiang, Yinzhou (Oncol Lett, 2017)
Calpains are a family of intracellular cysteine proteases involved in various biological processes. Previously, the family was identified to have abnormal expression in several types of malignant tumor. Calpain 6 was less well known; however, it was recently identified to be involved in the carcinogenesis of certain types of malignant tumor. However, the expression of calpain 6 in head and neck squamous cell carcinoma (HNSCC) remains unclear. A total of six datasets from the Gene Expression Omnibus (GEO) was analyzed and an association between calpain 6 expression levels and HNSCC was identified, with the expression of calpain 6 observed to be significantly decreased in HNSCC (P<0.01). However, the expression of calpain 6 may vary between distinct tumor stages of HNSCC. Furthermore, calpain 6 expression was positively associated with the survival rate in patients with HNSCC (P<0.05), with increased expression of calpain 6 associated with an improved survival outcome. Calpain 6 expression was analyzed using an HNSCC tissue microarray and these results were consistent with the statistical analysis of the bioinformatics data from the GEO, indicating that calpain 6 may be a tumor suppressor protein in HNSCC.